Enterobacter tabaci and Bacillus cereus as biocontrol agents against pathogenic Ralstonia solanacearum of eggplant - Abdul Malek, Azilah; Syd Ali, Nusaibah; Kadir, Jugah; Vadamalai, Ganesan; Mohd Saud, Halimi (Society for Indonesian Biodiversity, 2023)
Enterobacter tabaci and Bacillus cereus as biocontrol agents against pathogenic Ralstonia solanacearum of eggplant. Asian J Trop Biotechnol 20: 24-30. Over the world, Ralstonia solanacearum caused bacterial wilt disease is responsible for more than 90 of agricultural losses. Therefore, finding a potential biological control agent is extremely important, especially against R. solanacearum. The present study aimed to isolate, evaluate and identify potential endophytic bacteria to restrain R. solanacearum via in vitro antagonistic assay. A total of 116 endophytic bacteria were isolated, and 55 exhibited abilities to restrain R. solanacearum in vitro. However, only two isolates, UPMBC1 and UPMBE2, significantly inhibited R. solanacearum growth by 14.6 mm and 12.6 mm, respectively. Based on the cultural and morphological characteristics, UPMBC1 and UPMBE2 isolates exhibited similar characteristics as the other members of Enterobacteriaceae and Bacillaceae, respectively. Molecular results revealed that UPMBC1 was identified as Enterobacter tabaci and UPMBE2 as Bacillus cereus. Numerous efficient biological control agents were identified in the present investigation, with E. tabaci showing the greatest potential against R. solanacearum.